2006
DOI: 10.1016/j.jasms.2006.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfate position on heparin octasaccharide binding to CCL2 examined by tandem mass spectrometry

Abstract: Chemokine-glycosaminoglycan (GAG) interactions have been shown to be essential for in vivo chemokine signaling, which functions in such diverse processes as inflammation, development, and cancer metastasis. Despite the importance of these interactions, the saccharide sequence dependency of chemokine-GAG interactions is poorly understood. In a recent study, FT-ICR mass spectrometry was used to show that the chemokine CCL2 (monocyte chemoattractant protein 1) binds only to the 11-and 12-sulfated components of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Several methods have been developed to study GAG-protein interactions, including affinity chromatography, analytical ultracentrifugation, electrophoretic mobility shift assays, competition experiments, mass spectrometry-based approaches, isothermal titration calorimetry, and surface plasmon resonance (9)(10)(11)(12)(13)(14)(15)(16). Although powerful, these approaches are low throughput, often labor intensive, and require significant quantities of carbohydrate and/or protein.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been developed to study GAG-protein interactions, including affinity chromatography, analytical ultracentrifugation, electrophoretic mobility shift assays, competition experiments, mass spectrometry-based approaches, isothermal titration calorimetry, and surface plasmon resonance (9)(10)(11)(12)(13)(14)(15)(16). Although powerful, these approaches are low throughput, often labor intensive, and require significant quantities of carbohydrate and/or protein.…”
mentioning
confidence: 99%
“…Notably, no methods are available to rapidly screen various GAGs for their ability to assemble multimeric protein complexes. In addition, existing methods often require oligosaccharides or polysaccharides that are relatively homogeneous in chain length and charge density, such as fractionated heparin or chemically modified HS (11,12,14). As such, it has been difficult to study the interactions of proteins with other GAG classes and physiologically relevant GAG preparations, which are more heterogeneous and structurally diverse.…”
mentioning
confidence: 99%
“…Short lengths of GAGs can be analyzed by a combination of enzymatic digestion, tandem mass spectrometry (MS 2 and MS 3 ), and database searching [20]. While this approach can determine the pattern of modification (i.e., sulfation and acetylation), enzymatic digestion results in the formation of disaccharides containing C4 -C5 unsaturated uronic acid (⌬UA) at the nonreducing end (NRE), thereby converting glucuronic acid (GlcA) and iduronic acid (IdoA) into a single product (⌬UA) that eliminates chirality at C5 [21]. As the epimeric state of the hexuronic acid residues is thought to influence biological activity, it is important to be able to analyze GAG oligosaccharides which contain internal hexuronic acid residues that retain their chirality.…”
mentioning
confidence: 99%
“…McClellan et al have studied the fragmentation of regularly sulfated CS-oligosaccharides by use of SORI-CID FT-ICR MS [16] and Aguilan et al demonstrated the potential of Nano-ESI FT-ICR MS for the analysis of ␣-carrageenan sulfated oligosaccharides [31]. Recently, the noncovalent binding of chemokines to heparin octasaccharides and other potential ligands has been examined by use of high resolution FT-MS techniques [4,5,32].…”
mentioning
confidence: 99%